Properties of the fluid flow in a cylindrical duct with stenoses - Vovk, I.V.; Trotsenko, Ya.P. (Reports of the National Academy of Sciences of Ukraine, 2017)
The flow of a viscous incompressible fluid in a cylindrical duct with two serial contractions (stenoses) is studied by the numerical solution of unsteady Navier—Stokes equations. It is shown that an ensemble of vortex structures develops in the system that causes stable periodic self-sustained oscillations of the velocity profile at the outlet of the second stenosis orifice.